Empirical Political Theory (Ept): Characteristics, Strength-Weakness, And Challenges - Tonny Dian Effendi (Mandala: Jurnal Ilmu Hubungan Internasional, 2020)
This article discusses EPT in political science research in three explanations, namely characteristics, strength-weakness, and challenges. EPT has four critical characteristics, i.e., deductive, empirical, theoretic-methodologist, and replication.EPT, as part of the empiricism approach, covers scientific elements (Hypotetico-Deductive) and theoretical-methodological elements. It also allowsreplication., where it can be applied to case-comparison at one theoretical building. However, Formal Model (FM) scholars criticize EPT since it too adopts natural science models. It also depends on the data to provethe relationship or influence between variables in the hypothesis. Nevertheless, the relations do not reflect the causal inference. Nonetheless, EPT contributes significantly to the development of political science research, and replication can be used to build new theories, at least the case comparisons.